Educação profissional técnica de nivel médio no contexto do paradigma de acumulação flexível - Steffen, Euli Marlene (Universidade do Vale do Rio do Sinos, 2008)
This thesis is the result of the research of Doctorate on the program of Education Postgraduate at "Universidade do Vale do Rio dos Sinos - UNISINOS". The research carries out studies about Work-Education and focuses on the High-technical school and professional education. The general purpose of the research was to discuss the professional education of the technical course, through a review of the concept of professional qualification, considering: the process of professional formation, the learning process which happens during work and the convergence with decurrent requirements from the model of flexible accumulation. Therefore, it was focused the importance of knowing the process of the constitution of the technical professionals competences, which contribute for the ingression and maintenance at the work market. The study is about a Case with qualitative nature on which the subjects are the graduated students from the technical course, at UNED in Sapucaia do Sul (CEFET-RS) during the period of 1999-2004
Keywords: acumulação flexível; competências; dualismo estrutural; ensino médio; ensino técnico; formação integral; qualificação; educação profissional; competencies; flexible accumulation; integral formation; integration high-technical school; qualification; structural dualism; professional education; Ciências Humanas